Islam dan Sistem Ketatanegaraan: Analisis terhadap Ketiadaan Penetapan Bentuk Negara - Marsanul Cahyani; Hanifah Anom Orchidea; Putri Nor Zaitunah (Ahad: Multidisciplinary Journal of Islamic Studies, 2026)
This paper discusses the view that Islam does not require its followers to use one particular form of state, such as the caliphate system, and does not require the political unity of Muslims in one unified state. The state system belongs to the realm of muamalah which is ijtihadi and can change according to conditions, not worship which must follow strict provisions. There are no arguments in the Koran and hadith that require a particular state system, so that forms of state other than the caliphate, such as a unitary state based on Pancasila, can be accepted and considered in accordance with the principles of Islamic law. Apart from that, the perfect implementation of all Islamic law in Indonesia is not absolutely mandatory, considering the conditions and the benefit of the nation. Islamic law that has not been implemented does not make Muslims sin because of considerations of benefit and mafsadah. The National Conference of Alim Ulama Nahdlatul Ulama emphasized the importance of maintaining the Republic of Indonesia and Pancasila as a valid national agreement according to Islam, as well as encouraging the government to realize the benefit of the people with the principles of justice and divinity.